Changes in the Chemical and Sensory Profile of Coffea canephora var. Conilon Promoted by Carbonic Maceration - Gomes, Willian dos Santos; Pereira, Lucas Louzada; Filete, Cristhiane Altoé; Moreira, Taís Rizzo; Guarçoni, Rogério Carvalho; Catarina da Silva Oliveira, Emanuele; Moreli, Aldemar Polonini; Guimarães, Cleidiana Vieira; Simmer, Marinalva Maria Bratz; Júnior, Valdemar Lacerda; Romão, Wanderson; de Castro, Eustaquio Vinicius Ribeiro; et al. (Agronomy (Basel), 2022)
Among the different strategies adopted to improve the quality of Coffea canephora, fermentation is considered a promising technology to modulate the organoleptic characteristics of the beverage. Considering the possibility of providing a change in sensory profile through fermentation, this study aims to evaluate the chemical and sensory changes promoted by carbonic maceration in C. canephora whose effect is still unknown. The study was implemented in anaerobic conditions with different fermentation times (24, 48, 72, 96, and 120 h) and temperatures (18, 28, and 38 °C). The processed grains were subject to sensory analysis and medium infrared spectroscopy. Significant linear functional relationships were observed between total score and temperature for fermentation times of 24, 72, and 96 h and that the total score increased with fermentation temperature. Although a clear connection with sensory results was not observed, infrared analysis was able to point out important correlations with quality through stretches observed in infrared spectrum regions. Thus, there is feasibility of applying the carbonic maceration technique for grain processing of C. canephora.